Antiangiogenic gene therapy - Szary, Jarosław; Szala, Stanisław; Wilczyńska, Urszula (Contemporary Oncology/Współczesna Onkologia, 1999)
Several data show that transfer of sequences encoding angiostatin, endostatin or trucated receptors for VEGF can be used to inhibit tumor growth and metastasis.